AMINO-TERMINUS OF POLYMERASE BASIC-2 OF AVIAN INFLUENZA VIRUS OF H5N1 SUBTYPE ISOLATED FROM VARIOUS ANIMAL SPECIES IN INDONESIA - Yuniati Kencana, Gusti Ayu; Asmara, Widya; Rangga Tabbu, Charles; Kade Mahardika, I Gusti Ngurah (Jurnal Veteriner, 2008)
The information on pathogenicity and adaptation factors of avian influenza virus (AIV) in mammalsis very inportant in an effort to reduce the risk of avian influenza (AI) pandemic in the future. Polymerasegene complex appears to be the major factors for adaptation of AIV to certain animal species. A preliminarystudy on role of non-coding region (NCR) and amino-terminus of polymerase-basic 2 (PB2) is presented.Purified viral RNA of AIV isolated from chicken, duck, pig, and quail of Bali and Yogyakarta was reversetranscribed into cDNA and amplified using reverse transcriptase-polymerase chain reaction (RT-PCR)using PB-2 universal forward primer and specifically designed backward primer. The result showed thatall AIV’s H5N1 isolated from chicken, duck, quail, and pig, posed PB2 amino-terminus typical for IndonesianAIV H5N1. However, polymorphic amino acids of the protein fragment did not show any species specificmotive, with the exception of the pig isolate Sw/Tabanan/2006 which had specific substitution of D16E,H17Q, M40I, and H124Y.
Keywords: PB2 gene, avian influenza, H5N1, Indonesia